History's mysteries Disc 1 Roswell: Secrets unveiled (DVD/videorecording) : Crop Circle Controversy - Kent, Arthur, 1953-; Ackroyd, David; Arts and Entertainment Network; A & E Home Video (Firm); New Video Group; History Channel (Television network) (New York, N.Y. : A & E Television Networks : Distributed by New Video Group, 2011)
Pick up where the textbooks leave off with History's mysteries and explore the stories, events, legends, and myths that have aroused curiosity, inspired wonder, and incited debate throughout the ages.
Roswell: secrets unveiled -- Crop circle controversy.
Originally broadcast as a segment of the series History's mysteries.
Title on spine and discs: Classics.
Executive producers, Robb Weller, Gary H. Grossman ; produced by John Joseph.
Arthur Kent, host ; David Ackroyd, narrator.
DVD, Dolby digital sound.
108613
Keywords: 1947; Roswell Incident, Roswell, N.M., 1947.; Unidentified flying objects -- Sightings and encounters -- New Mexico -- Roswell; Crop circles; DVDs; New Mexico -- Roswell; Television programs